Dental erosion from diagnosis to therapy - Lussi, Adrian (Monographs in oral science, 2006)
Erosive tooth wear is a multifactorial condition of growing concern to the clinician and is a subject of extensive research. This book is the first which deals in such detail with dental erosion. It presents the whole spectrum of views on the issue, from the molecular level to behavioral aspects, as well as trends in society. The multifactorial etiological pattern of erosive tooth wear is emphasized and is a strand connecting the different chapters of the book. Definition, diagnosis, prevalence, incidence and chemistry of dental erosion are discussed in the first part of the publication. Further, topics like extrinsic and intrinsic causes of dental erosion are covered and a chapter is devoted to dental erosion in children. Methods of assessment are presented and critically evaluated. The book concludes with themes on dentinal hypersensitivity, risk assessment and preventive measures and restorative options for erosive lesions. This publication is not only highly recommended to faculty members, researchers and dental students, but also to practitioners and other dental professionals who are committed to the prevention and treatment of dental erosion